Grid Integration of Solar PV Using UPQC with Differential Inverter Control - Kondalu, M.; Kumar, Alupula Varun (Journal of Neonatal Surgery, 2025)
Ensuring voltage stability in integrated photovoltaic (PV) distribution systems is essential for the reliable operation of all connected devices within the network. One of the primary challenges in PV system integration is maintaining a stable voltage profile. This study focuses on stabilizing the voltage profile for a sensitive load of 22 kVA. A single-phase distribution system with PV integration serves as the basis for this analysis. The innovation lies in the use of differential inverters functioning as both a dynamic voltage restorer and a distribution static synchronous compensator within a unified power quality conditioner (UPQC). A key benefit of employing differential inverters is their capability for active power decoupling. The main goal of this research is to connect a 10-kW solar PV system to the distribution network using the proposed UPQC configuration. The study identifies and evaluates the most effective control strategy for the UPQC integrated with a battery energy storage system. A 20 kVA UPQC is designed specifically for enhancing voltage stability and supporting PV integration in the distribution network, with assumptions of constant frequency, voltage, and reactance-to-resistance (X/R) ratio.